2013
DOI: 10.1371/journal.pgen.1003630
|View full text |Cite
|
Sign up to set email alerts
|

Fine Time Course Expression Analysis Identifies Cascades of Activation and Repression and Maps a Putative Regulator of Mammalian Sex Determination

Abstract: In vertebrates, primary sex determination refers to the decision within a bipotential organ precursor to differentiate as a testis or ovary. Bifurcation of organ fate begins between embryonic day (E) 11.0–E12.0 in mice and likely involves a dynamic transcription network that is poorly understood. To elucidate the first steps of sexual fate specification, we profiled the XX and XY gonad transcriptomes at fine granularity during this period and resolved cascades of gene activation and repression. C57BL/6J (B6) X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
108
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 59 publications
(88 reference statements)
14
108
1
Order By: Relevance
“…Instead, sexual dimorphism is initiated in the early gonad supporting cells, a single cell lineage that differentiates into Sertoli (XY) (Sekido et al, 2004) or pregranulosa (XX) cells (Albrecht and Eicher, 2001;Mork et al, 2012). Prior to sex determination, XX and XY supporting cells are bipotential and express nearly all genes at similar levels, with minor differences limited to genes on the X and Y chromosomes (Nef et al, 2003;Munger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, sexual dimorphism is initiated in the early gonad supporting cells, a single cell lineage that differentiates into Sertoli (XY) (Sekido et al, 2004) or pregranulosa (XX) cells (Albrecht and Eicher, 2001;Mork et al, 2012). Prior to sex determination, XX and XY supporting cells are bipotential and express nearly all genes at similar levels, with minor differences limited to genes on the X and Y chromosomes (Nef et al, 2003;Munger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sry is transiently expressed and many SRY-binding sites are subsequently bound by its downstream target SOX9 (Li et al, 2014). SRY and SOX9 control the differentiation of Sertoli cells by triggering a dramatic transcriptional reprogramming of bipotential progenitor cells within just 24 h, leading to the upregulation of over 200 genes important for Sertoli cell development and downregulation of ∼100 pregranulosa cell-expressed genes that were expressed at the bipotential stage (Munger et al, 2013). In the absence of Sry, XX supporting cells differentiate to pregranulosa cells, but in contrast to the dramatic transcriptional changes that accompany Sertoli cell specification, pregranulosa cell differentiation proceeds with fewer transcriptional changes consistent with the finding that undifferentiated XX and XY supporting cells are initially transcriptionally biased toward ovarian fate (Jameson et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…An interaction between the endoderm and the ectoderm at the cloacal membrane may be an important step in induction of budding. 5,6,24,25,26 Longstanding dogma is that the sexually indifferent genital tubercle is masculinized by androgens and that feminization is a default state that occurs in the absence of androgen activity, though recent studies of ER mutants have falsified this hypothesis. 5 Thus, in the absence of ERa activity, female external genitalia are partially masculinized, suggesting that estrogen is required for inhibition of clitoral growth in females.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the intriguing possibility that basal levels of androgen in females can lead to masculinization of the genital tubercle, and estrogen is required to counter the influence of androgen. 5,6,26,27 Mutations in the androgen receptor (as in the testicular feminization or Tfm mutation), by contrast, cause feminization of the external genitalia, such that Tfm mutant male genitalia are indistinguishable from female genitalia. 26 Mutations in the gene that encodes 5a-reductase 2, which converts testosterone to dihydrotestosterone, also disrupt masculinization of the genital tubercle and cause defects ranging from hypospadias and micropenis to complete feminization of the external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could help elucidate the molecular control of primordial follicle assembly, as well as provide potential targets for ovarian disease treatment. In order to elucidate the first steps of sexual specification, a recent study (Munger et al, 2013) used transcriptomic profiling and probabilistic models to predict novel regulatory genes involved in the process in mice. They showed that Lmo4 (Lim-domain only 4) is a novel regulator of sex determination upstream of SF1 (steroidogenic factor 1).…”
Section: Approaches To Integrate Omics and Other Datamentioning
confidence: 99%